2021
DOI: 10.1002/ajmg.a.62197
|View full text |Cite
|
Sign up to set email alerts
|

Subtle differences in autonomic symptoms in people diagnosed with hypermobile Ehlers–Danlos syndrome and hypermobility spectrum disorders

Abstract: The hypermobile Ehlers–Danlos syndrome (hEDS) GENE study is a multicenter, cohort study with the goal to identify genes associated with hypermobile EDS. Of the 148 people enrolled in the hEDS GENE study, 98 meet the 2017 hEDS criteria, 27 have a hypermobility spectrum disorder (HSD) and 23 are asymptomatic family members. More than 80% of participants are female with an average age of 41 years. Each participant has completed seven questionnaires to quantify disease‐related symptomatology. People with hypermobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 65 publications
(106 reference statements)
0
21
0
Order By: Relevance
“…These JHM-associated comorbidities include chronic fatigue, pelvic floor problems, bladder dysfunction, increased susceptibility to osteoarthritis, various dysautonomic features (e.g., postural orthostatic tachycardia syndrome, gastrointestinal dysfunction), alterations of the immune system, headache/migraine, sleep disorders, behavioral disturbances, and psychological distress [ 1 , 2 , 3 , 4 , 5 , 6 ]. After the publication of the updated diagnostic criteria, several authors raised serious doubts about their limits, and it is still debated if hEDS and HSD are distinct clinical entities rather than part of a phenotypic spectrum that require a similar pattern of multidisciplinary intervention [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Considering the overlapping clinical presentation of hEDS and HSD patients and the absence of any objective and validated diagnostic biomarker, many researchers currently use the terms hEDS and HSD interchangeably and these two diagnostic labels are often grouped together as hEDS/HSD [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These JHM-associated comorbidities include chronic fatigue, pelvic floor problems, bladder dysfunction, increased susceptibility to osteoarthritis, various dysautonomic features (e.g., postural orthostatic tachycardia syndrome, gastrointestinal dysfunction), alterations of the immune system, headache/migraine, sleep disorders, behavioral disturbances, and psychological distress [ 1 , 2 , 3 , 4 , 5 , 6 ]. After the publication of the updated diagnostic criteria, several authors raised serious doubts about their limits, and it is still debated if hEDS and HSD are distinct clinical entities rather than part of a phenotypic spectrum that require a similar pattern of multidisciplinary intervention [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Considering the overlapping clinical presentation of hEDS and HSD patients and the absence of any objective and validated diagnostic biomarker, many researchers currently use the terms hEDS and HSD interchangeably and these two diagnostic labels are often grouped together as hEDS/HSD [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hypermobile EDS is known to present with an autonomic dysfunction, such as functional gastrointestinal disorders and orthostatic intolerance, including postural orthostatic tachycardia syndrome. [52][53][54][55][56][57] These autonomic symptoms are frequent extraarticular manifestations of hypermobile EDS and contribute to the disease burden. 58 Several previous studies confirmed the presence of cardiovascular and sudomotor dysfunction, and many upper and lower gastrointestinal symptoms increased along with worsened severity of joint hypermobility syndrome phenotype.…”
Section: Autonomi C Dys Fun C Ti On In G Ene Tic D Is E a S E Smentioning
confidence: 99%
“…58 Several previous studies confirmed the presence of cardiovascular and sudomotor dysfunction, and many upper and lower gastrointestinal symptoms increased along with worsened severity of joint hypermobility syndrome phenotype. [52][53][54][55][56][57][58] However, it is still unclear how autonomic dysfunction occurs in EDS. Brooks et al 53 reported that patients hospitalized with EDS were 3.88 times more likely to have a food allergy and 6.16 times more likely to have cardiovascular complications such as mitral valve disorders, aortic aneurysm, and cardiac dysrhythmias than hospitalized patients without EDS.…”
Section: Autonomi C Dys Fun C Ti On In G Ene Tic D Is E a S E Smentioning
confidence: 99%
See 2 more Smart Citations